Does ESG certification add firm value? - Wong, Woei Chyuan; Batten, Jonathan A.; Ahmad, Abd Halim @ Hamilton; Mohamed Arshad, Shamsul Bahrain; Nordin, Sabariah; Abdul Adzis, Azira (Elsevier Inc., 2020)
This paper examines the impact of environmental, social and governance (ESG) certification on Malaysian firms. The analysis shows that ESG certification lowers a firm's cost of capital, while Tobin's Q increases significantly. These findings, while consistent with existing studies in developed economies, demonstrate the value enhancement from corporate social responsibility disclosure by firms in emerging and developing nations. Overall, the study confirms the benefits to stakeholders from firms pursuing an ESG agenda.